Safety of licensed vaccines in HIV-infected persons: a systematic review protocol - Kagina, Benjamin M (BioMed Central, 2014)
BACKGROUND: Safety of vaccines remains a cornerstone of building public trust on the use of these cost-effective and life-saving public health interventions. In some settings, particularly Sub-Saharan Africa, there is a high prevalence of HIV infection and a high burden of vaccine-preventable diseases. There is evidence suggesting that the immunity induced by some commonly used vaccines is not durable in HIV-infected persons, and therefore, repeated vaccination may be considered to ensure optimal vaccine-induced immunity in this population. However, some vaccines, particularly the live vaccines, may be unsafe in HIV-infected persons. There is lack of evidence on the safety profile of commonly used vaccines among HIV-infected persons. We are therefore conducting a systematic review to assess the safety profile of routine vaccines administered to HIV-infected persons. METHODS/DESIGN: We will select studies conducted in any setting where licensed and effective vaccines were administered to HIV-infected persons. We will search for eligible studies in PubMed, Web of Science, Cochrane Central Register of Controlled Trials (CENTRAL), Scopus, Africa-Wide, PDQ-Evidence and CINAHL as well as reference lists of relevant publications. We will screen search outputs, select studies and extract data in duplicate, resolving discrepancies by discussion and consensus. DISCUSSION: Globally, immunisation is a major public health strategy to mitigate morbidity and mortality caused by various infectious disease-causing agents. In general, there are efforts to increase vaccination coverage worldwide, and for these efforts to be successful, safety of the vaccines is paramount, even among people living with HIV, who in some situations may require repeated vaccination. Results from this systematic review will be discussed in the context of the safety of routine vaccines among HIV-infected persons. From the safety perspective, we will also discuss whether repeat vaccination strategies may be feasible among HIV-infected persons. SYSTEMATIC REVIEW REGISTRATION: PROSPERO CRD42014009794.